LOCAL BARLEY ACCESSIONS FROM ETHIOPIA RESISTANT TO POWDERY MILDEW - N. V. Alpatieva; R. A. Abdullaev; I. N. Anisimova; N. K. Gubareva; O. N. Kovaleva; E. E. Radchenko (Труды по прикладной ботанике, генетике и селекции)
The mlo11 allele associated with the loss of function of the Mlo locus and controlling mildew resistance in the majority of modern barley cultivars was identified in Ethiopian barley landraces. Twenty-seven accessions from Ethiopia were studied during laboratory experiments which resulted in identifying k-5448 as an accession resistant to powdery mildew. Three accessions (k-8555, k-8682 k-17554) were heterogeneous by the studied trait. With the help of molecular markers we showed that the resistant components of the selected forms are protected by the mlo11 gene.